Challenges encountered by functionally illiterate consumers in the Kumasi metropolis, Ghana - Kusi-Mensah, Kwaku; Cook, Gina, 1970-; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This study is concerned with how illiteracy impact consumers when navigating through the market place to have their needs met.These effects are researched in the Kumasi metropolis in the Ashanti Region of Ghana. The overall goal of the thesis is to investigate the problems that functionally illiterate consumers encounter when navigating through the Marketplace.The results show that functionally illiterate consumers at the Kumasi metropolis do face problems when navigating through the market place and that these problems are related to the retail marketing mix such as product, price, place, people, promotion and process.
Vedoucí práce: Gina Cook
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses